Community Empowerment In Applying The Sunnah Of The Prophet: Dhikr To Reduce Anxiety During The Covid-19 Pandemic: Pemberdayaan Masyarakat Dalam Mengaplikasikan Sunnah Rasul: Dzikir Untuk Menurunkan Kecemasan Di Masa Pandemi Covid-19 (JURNAL UNEJ, 2024)
The trigger for anxiety in the community during the COVID-19 pandemic was stress due to social isolation or physical distancing during Large-Scale Social Restrictions (PSBB). Excessive anxiety during quarantine can increase the risk of anxiety, depression, and post-traumatic stress symptoms. One way to deal with anxiety problems during the Covid-19 pandemic is to use a non-pharmacological approach, namely the application of the Sunnah of the Prophet: Dhikr is one form of activity or activity that has been exemplified by the Prophet Muhammad. The purpose of this community service is to reduce the anxiety of the Muslim community at the Wonolapan Posyandu. The method of implementing this community service uses the lecture method and leaflet media. Community service will be held at the Pucangan Kartasura Posyandu on Sunday, 27 June 2021. The community at the end of the activity was able to explain simply the meaning of the Sunnah of the Prophet, the purpose of the Sunnah of the Prophet, whenever he performs the Sunnah of the Prophet, stages of dhikr in the Sunnah of the Apostle (100%), the percentage of community activity in counseling the Sunnah of the Apostle: Dhikr is (95%). This shows that the implementation of counseling can increase public knowledge about the management of anxiety during the COVID-19 pandemic.